An observational, prospective, multicenter study on the utilization and effectiveness of elbasvir–grazoprevir treatment association for chronic hepatitis C in France (ZEPHYR study). Issue 1 (5th December 2022) - Bronowicki, Jean‐Pierre; Miailhes, Patrick; Hanslik, Bertrand; Ouzan, Denis; Larrey, Dominique; Riachi, Ghassan; Truchi, Régine; Jouannaud, Vincent; Pospait, Dan; Abergel, Armand; Causse, Xavier; Perot, Stéphanie; et al.
Abstract: Background and Aim: The efficacy and safety profiles of elbasvir–grazoprevir (EBR/GZR) has been established in more than 10 clinical trials. However, the characteristics of patients treated in routine clinical practice may differ. The present study was therefore designed to assess the real‐life effectiveness of EBR/GZR therapy in the general population and among subgroups with a high hepatitis C virus (HCV) prevalence in France. Methods: The Zephyr study was designed as a French, multicentre, prospective, observational study on EBR/GZR use and effectiveness in current practice in chronic hepatitis C patients. These results are based on data regarding the adult patients who received at least one dose of EBR/GZR between December 2017 and June 2019 in 67 French hospitals and clinics. Results: Overall, 478 patients were included. The Full Analysis Set corresponded to the 467 patients who met all the inclusion criteria and none of the exclusion criteria. Gender was balanced and the mean age was 55.7 ± 13.3 years. The patients were mainly treatment‐naive (89.5%) and infected with Genotype 1b (70.4%). Among the 75 patients with HCV Gt1a genotype, 56% had HCV RNA ≥ 800, 000 IU/ml. F3–F4 fibrosis stage involved 24.2% of our population. Our subgroups were distributed among 110 migrants (23.6%), 58 (15.3%) using opioid agonist treatment, including people who inject drugs, 30 (6.8%) with chronic kidney disease Stages 3–5, 9 (1.9%) with an inherited blood disorder, and 4 (0.9%) coinfected with HIV. The remaining 269 (58.7%) were included in the general population subgroup. Overall, sustained virologic response 12 weeks after the end of treatment reached 98.0% and remained consistent among genotype, HCV RNA values, fibrosis stage, and the subgroup of interest. The rate of Alcohol Use Disorders Identification Test‐Consumption​​​ and Life Habit questionnaire completion was high at each visit, with data suggesting alcohol consumption decrease and an improvement in quality of life. Conclusions: Using real‐world evidence data on a French population representative of HCV patients, we confirmed the results obtained during EBR/GZR development program.